Native and invasive taxa on the Pacific coast of South America: Impacts on aquaculture, traceability and biodiversity of blue mussels (Mytilus spp.). (20th October 2017) - Larraín, Maria A.; Zbawicka, Malgorzata; Araneda, Cristian; Gardner, Jonathan P. A.; Wenne, Roman
Abstract: Gaining new knowledge of the native distributions of species (phylogeography) is more and more difficult in a world affected by anthropogenic disturbance, in particular by species translocations. Increasingly, molecular markers are required to support decisions about the taxonomy of native vs. introduced species, and the existence of their hybrids, to answer phylogeographic questions. In many fields, including aquaculture, traceability and food security, taxonomic and phylogeographic knowledge is key to the successful management and conservation of biodiversity. The Pacific coast of Chile is one of the last regions without a clear and agreed understanding of the taxonomy and systematics of smooth‐shelled blue mussels of the genus Mytilus . A panel of 49 bi‐allelic single nucleotide polymorphisms (SNPs) was genotyped in 338 Mytilus individuals collected from nine Chilean and five reference populations. All analyses confirmed the hypothesis that the native Chilean blue mussel is genetically distinct from the reference species M. edulis, M. galloprovincialis and M. trossulus . These results support the hypothesis of a unique evolutionary history of the native Chilean blue mussel on the Pacific coast of South America. It is therefore concluded that the native blue mussel from Chile should be recognized as M. chilensis Hupé 1854. We confirmed a recent Mediterranean origin of introduced M. galloprovincialis on the coast of Chile. This knowledge advances the understanding of global phylogeography of blue mussels and their bioinvasions and harmonizes taxonomy in the context of aquaculture production, seafood traceability, labelling and trade.